2017
DOI: 10.1038/ncomms14837
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting protein drugs for the treatment of ocular diseases

Abstract: Protein drugs that neutralize vascular endothelial growth factor (VEGF), such as aflibercept or ranibizumab, rescue vision in patients with retinal vascular diseases. Nonetheless, optimal visual outcomes require intraocular injections as frequently as every month. Here we report a method to extend the intravitreal half-life of protein drugs as an alternative to either encapsulation or chemical modifications with polymers. We combine a 97-amino-acid peptide of human origin that binds hyaluronan, a major macromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 17 publications
(18 reference statements)
1
52
0
Order By: Relevance
“…[50][51][52][53][54] In the same way, under retinal angiogenesis including both OIR and CNV models, vascular hyperpermeability occurred. 3,[55][56][57][58] In this study, we confirmed that VEGFinduced hyperpermeability in HRMECs (Fig. 1C) and laser irradiation developed fluorescein leakage in the FA analysis in monkeys (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…[50][51][52][53][54] In the same way, under retinal angiogenesis including both OIR and CNV models, vascular hyperpermeability occurred. 3,[55][56][57][58] In this study, we confirmed that VEGFinduced hyperpermeability in HRMECs (Fig. 1C) and laser irradiation developed fluorescein leakage in the FA analysis in monkeys (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The results above indicate that antibodies can be tracked non-invasively and longitudinally in large animals and potentially in humans, which will enable personalized therapeutics titration in the eye. We wanted to further characterize the technique by labeling an internal LAAVA construct designed to reside longer in the vitreous than current antibodies and developed for retinal diseases 6 . Immediately after IVT injection, the labeled LAAVA showed the same agglomerate pattern as ranibizumab or IRDye800CW alone, but in contrast to the other two products, it never homogenized within the vitreous after injection (Fig.…”
Section: Kinetics Of Labeled Ranibizumab In Different Compartmentsmentioning
confidence: 99%
“…Furthermore, these assays often lack spatial information (due to homogenized tissue-based measurements) and provide low temporal resolution (only a few time points are usually analyzed). With the advent of novel approaches to extend the retention time of biologics at the retina, such as PEGylated or hyaluronan-binding antibodies 6,7 , it is imperative to develop novel non-invasive translatable platforms that can directly determine the ocular distribution of long-acting agents in the human eye.…”
mentioning
confidence: 99%
“…Affinity-based DDS is often based on interactions between an API and its dosage form but can also be related to the interaction of an API with a tissue. Affinity-based DDS is not solely dependent on the properties of the polymer matrix (e.g., pore size and degradation rate) [ 151 ], complicated manufacturing steps and surgical administration [ 152 ]. A polymer formulation can be modified to give a higher affinity towards drug molecules to increase the drug loading and hence, prolong the drug duration of action [ 153 ].…”
Section: General Strategies To Increase Duration Of Actionmentioning
confidence: 99%
“…Affinity-based systems have also been explored for prolonged ocular delivery of proteins. Components of the vitreous such as HA [ 152 ] and type II collagen [ 324 , 325 ], as well as molecules in the eye such as melanin [ 326 , 327 ] and components of the inner limiting membrane (ILM) [ 328 ], have been identified as potential targets for ocular binding affinity. Researchers from Novartis have characterised a hyaluronan-binding peptide (HABP) fused to the heavy chain or Fc region of a number of proteins (Fab, IgG and scFv) for the development of long-acting anti-VEGF drugs (LAVAs).…”
Section: Polypeptide Deliverymentioning
confidence: 99%